2012
DOI: 10.3126/jcmsn.v8i2.6834
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography scan in the evaluation of patients with stroke

Abstract: ABSTRACT ABSTRACT ABSTRACTCerebrovascular accident is a frequent cause of death and disability in most parts of the globe. The incidence of cerebrovascular diseases increases with age and the number of strokes is projected to increase as the elderly population grows. This study was undertaken to determine the type of stroke and also to relate the risks factors associated with stroke. Hundred consecutive patients presenting with stroke in the emergency department / neurology clinic were subjected to computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…This was also seen in study done by Jose´ Luis et al, 31 in which the most common locations of ICHs were lobar in (55%), second most common site was thalamoganglionic and ventricular with 2 cases, which was shown in book Neuroimaging -Methods, 33 in which most common site of hemorrhage was lobar followed by thalamoganglionic. In group-2 most common site of hemorrhage was thalamoganglionic (77%) followed by lobar (35%), similar trend was seen in study done by P. K. Chhetri et al 34 and Pipat Chiewvit et al 35 .…”
Section: Topographic Distribution Of Infarct According To Age Groupssupporting
confidence: 82%
“…This was also seen in study done by Jose´ Luis et al, 31 in which the most common locations of ICHs were lobar in (55%), second most common site was thalamoganglionic and ventricular with 2 cases, which was shown in book Neuroimaging -Methods, 33 in which most common site of hemorrhage was lobar followed by thalamoganglionic. In group-2 most common site of hemorrhage was thalamoganglionic (77%) followed by lobar (35%), similar trend was seen in study done by P. K. Chhetri et al 34 and Pipat Chiewvit et al 35 .…”
Section: Topographic Distribution Of Infarct According To Age Groupssupporting
confidence: 82%
“…This study also observed that the most common vascular territory involved is MCA territory seen in 69 patients (62.2%) while the least is the ACA territory (0.9%). This is similar to the report of a study conducted by Chhetri et al 15 who reported a 75% involvement of the MCA and 10% of ACA. The preponderant involvement of the MCA is probably because the MCA is the largest cerebral vessel and the one in direct continuity with the internal carotid artery thus prone to direct transmission of thrombus.…”
Section: Articlesupporting
confidence: 92%
“…1 Adeyekun et al 14 reported the incidence of ischaemic stroke as 73.8% of all patients with stroke in Nigerians. In the same vain, higher incidence of ischaemic stroke was found in studies conducted by Chhetri et al 15 in Asia and Kehinde et al 16 in Nigeria.…”
Section: Introductionmentioning
confidence: 58%
“…Lacunar infarction is a deep subcortical infarction that usually involves the perforation of an artery in the deep gray matter and brainstem. Lacunar infarcts are usually less than 1 cm in dimensions and not more than 1.5 cm in diameter (21). The majority of lacunar infarcts are located in the area of the lenticular branches as well as the deep perforator medullary branches of the anterior, the branches thalamoperforating, thalamogeniculate, and middle cerebral arteries of the cerebral arteries, and the paramedian branches of the basilar arteries (18).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-three patients (91.66%) faced primary intracranial hemorrhage. The most frequently affected areas were the basal ganglia and the internal capsule (66.66%), followed by the thalamus (21.21%), the temporoparietal lobe (9.09%), and the posterior fossa (3.03%) (21). Supratentorial ICH is divided into lobar ICH (the center of the bleeding zone is in the white-gray matter junction) and deep ICH (the center of the bleeding zone in the basal ganglia and thalamus).…”
Section: Methodsmentioning
confidence: 99%